The Effectiveness of Mind-Map Method to Improve Students’ Learning Achievement Motivation and Interest on Subject Islamic Civilization at Class 4B of Institute Teacher Training Collage at Darussalam Gontor Modern Islamic Boarding School of Campus 2 - Safiruddin Al Baqi; Heru Chakra Setiawan (Educan : Jurnal Pendidikan Islam, 2020)
This classroom action research was motivated by the low scores of students ITTC of Class 4B in Darussalam Gontor Modern Islamic Boarding School of Campus 2 on the Subject Islamic civilization, especially on aspects of student learning achievement which caused by lack of motivation and interest in learning caused by several factors one of which is the lack of innovation of teaching used by the teacher who only use the lecturing method. This research aims to improve student learning achievement and determine the effect of interest and motivation on student learning achievement and to test the effectiveness of Mind-map methods. In the discussion on Nasy’at Hadarah Al-Islamiyyah in cycle 1 and Ushul Hadarah Al-Islamiyyah in cycle 2, using the Mind-map method. This research was conducted from January to February 2019, held in class 4B ITTC in Darussalam Gontor Modern Islamic Boarding School of Campus 2. This type of research is Classroom Action Research with one pre-cycle and two cycles consisting of two meetings in one cycle, each cycle consists of: planning, implementation, observation and reflection. Data collection techniques and tools, in this research, used descriptive analysis techniques for data in the form of student work documents, lists of values, and observation sheets. The results showed that with the Mind-map method was a pleasant learning atmosphere. Student learning achievement increased, there was increase cycle 1 to Cycle 2 then, in the first cycle the number of students who received complete grades was 12 students or 40%, Grades not complete in cycle 1 is 26 students or 86.6%, while in cycle 2 there is an increase in complete value that is all students in class 4B increased to reach 100%. . As for the aspects of the influence of motivation and ask for student learning achievement, there was an increase in motivation and interest, in the pre-cycle, the average of interest score 58.03 and motivation 54.03, in cycle 1 the average of interest scores 58.56 and motivation 53.8 despite a decrease in motivation scores from pre-cycle to cycle 1, in the second cycle, there was an increase in scores, at the last cycle the average of interest 58.96 and motivation 54.9, it was concluded that the Mind-map method can improve student learning achievement. Mind-map method was influential in increasing student interest and motivation in learning.